Antibiotic de-escalation patterns and outcomes in critically ill patients with suspected pneumonia as informed by bronchoalveolar lavage results - Mengou Zhu; Chiagozie I. Pickens; Nikolay S. Markov; Anna Pawlowski; Mengjia Kang; Luke V. Rasmussen; James M. Walter; Nandita R. Nadig; Benjamin D. Singer; Richard G. Wunderink; Catherine A. Gao (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Purpose Antibiotic stewardship in critically ill pneumonia patients is crucial yet challenging, partly due to the limitations of noninvasive diagnostic tests. This study reports an antibiotic de-escalation pattern informed by bronchoalveolar lavage (BAL) results, incorporating quantitative cultures and multiplex PCR rapid diagnostic tests. Methods We analyzed data from SCRIPT, a single-center prospective cohort study of mechanically ventilated patients who underwent a BAL for suspected pneumonia. We used the Narrow Antibiotic Therapy (NAT) score to quantify day-by-day antibiotic prescription patterns for each suspected pneumonia episode etiology (bacterial, viral, mixed bacterial/viral, microbiology-negative, and non-pneumonia control). The primary outcome was a composite of in-hospital mortality, discharge to hospice, or requiring lung transplantation during hospitalization, which we referred to as unfavorable outcomes. The secondary outcomes were duration of ICU stay, duration of intubation, and Clostridium difficile during admission. Outcomes were compared across pneumonia etiologies with the Mann–Whitney U test and Fisher’s exact test. Results Among 686 patients (409 men, 276 women) with 927 pneumonia episodes, NAT score analysis showed consistent antibiotic de-escalation in all pneumonia etiologies except resistant bacterial pneumonia. Microbiology-negative pneumonia was treated similarly to susceptible bacterial pneumonia. 44% viral episodes had antibiotic cessation by post-BAL day 5. Unfavorable outcomes were comparable across all pneumonia etiologies. Patients with viral and mixed bacterial/viral pneumonia had longer durations of ICU stay and intubation. Clostridium difficile was detected in 14 (2%) patients . Conclusions BAL quantitative cultures and multiplex PCR rapid diagnostic tests resulted in prompt antibiotic de-escalation in critically ill pneumonia patients. There was no evidence of increased unfavorable outcomes.